Inequalities for Generalized Grötzsch Ring Function - Zhao, Tie-Hong; Bhayo, Barkat Ali; Chu, Yu-Ming (Computational methods and function theory, 2022)
In this paper, we deal with the generalized Grötzsch ring function μ a ( r ) for r ∈ ( 0 , 1 ) in the theory of the Ramanujan generalized modular equation and present new inequalities for μ a ( r ) .